2013
DOI: 10.1371/journal.pone.0068125
|View full text |Cite
|
Sign up to set email alerts
|

Putative Structural and Functional Coupling of the Mitochondrial BKCa Channel to the Respiratory Chain

Abstract: Potassium channels have been found in the inner mitochondrial membranes of various cells. These channels regulate the mitochondrial membrane potential, the matrix volume and respiration. The activation of these channels is cytoprotective. In our study, the single-channel activity of a large-conductance Ca2+-regulated potassium channel (mitoBKCa channel) was measured by patch-clamping mitoplasts isolated from the human astrocytoma (glioblastoma) U-87 MG cell line. A potassium-selective current was recorded with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 38 publications
6
109
0
Order By: Relevance
“…Other studies performed at higher Ca 2+ concentrations (200 μM) led, as expected, to V 1/2 (−20 mV) more negative compared to the value estimated for the control channel in the present case (11 mV) (Bednarczyk et al, 2013). More importantly is the observation that channels from our Aβ rat model showed a left shift in V 1/2 of~6 mV relative to controls, suggesting an intrinsic change in the channel gating mechanism.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Other studies performed at higher Ca 2+ concentrations (200 μM) led, as expected, to V 1/2 (−20 mV) more negative compared to the value estimated for the control channel in the present case (11 mV) (Bednarczyk et al, 2013). More importantly is the observation that channels from our Aβ rat model showed a left shift in V 1/2 of~6 mV relative to controls, suggesting an intrinsic change in the channel gating mechanism.…”
Section: Discussionsupporting
confidence: 85%
“…In fact, interactions between BK Ca α/β4 subunits may involve other protein constituents not present when channels are incorporated in a lipid bilayer. Notably a recent study on the mitoBK Ca channel in astrocytoma U-87 MG cells suggests a structural and functional coupling between the mitoBK Ca channel with the mitochondrial respiratory chain that could include β4 (Bednarczyk et al, 2013). A modification of the β4 expression level could have under these conditions an important impact on the mitochondrial functionality.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear whether the mitochondrial or the plasma membrane BK Ca channel is the major mediator of pharmacological preconditioning. Both blockers are affect mitochondrial channel activity (Bednarczyk et al 2013a(Bednarczyk et al , 2013b, but organotipic hippocampal slice culture (applied in this manuscript) may differentiate access of these modulators to plasma membrane or mitochondrial BK Ca channels.…”
Section: Discussionmentioning
confidence: 99%
“…With antibodies raised against the plasma membrane BK Ca channels, we have identified a pore-forming a subunit and regulatory b2 subunit of the channel in the endothelial inner mitochondrial membrane. Our findings indicate a possible structural and functional coupling of the mitoBK Ca channel with the mammalian mitochondrial respiratory chain [55]. In addition, we have shown that hemin inhibits mitoBK Ca and partially abolishes some of the cytoprotective properties of potassium channel opening [56].…”
Section: Potassium Channelsmentioning
confidence: 59%